Psychometric validation of type 2 Diabetes Distress Assessment System in an Indian type 2 diabetes population - Baby Sharma; Pramod Tripathi; Nidhi Kadam; Diptika Tiwari; Anagha Vyawahare; Thejas Kathrikolly; Malhar Ganla (Scientific Reports)
Abstract Diabetes distress (DD) significantly burdens and negatively impacts self-management and health outcomes in patients with type 2 diabetes (T2D). Early detection and management of DD are crucial for effective T2D management. The Diabetes Distress Assessment System (T2-DDAS) is a recently validated tool for measuring DD, but its psychometric properties in non-Western populations, such as India, have not been evaluated. This study aimed to assess the validity and reliability of T2-DDAS in Indian patients with T2D. Data from 408 T2D patients enrolled in a one-year diabetes management program at the Freedom from Diabetes Clinic in Pune, India, from January to March 2024, were analyzed. Sociodemographic characteristics, medical history, and anthropometric parameters were extracted from existing records. T2-DDAS, previously validated in a Western population, was administered. Statistical analyses included descriptive statistics, Principal Component Analysis (PCA), Exploratory Factor Analysis (EFA), Confirmatory Factor Analysis (CFA), and Structural Equation Modeling (SEM), using IBM SPSS, R, and AMOS software. The T2-DDAS demonstrated good internal consistency (Cronbach’s α = 0.91). CFA yielded satisfactory fit indices (χ² = 1036.92, RMSEA = 0.07, TLI = 0.905, CFI = 0.918), supporting the construct validity of T2-DDAS for the Indian population. The T2-DDAS is a valid and reliable tool for assessing DD in Indian patients with T2D.